Effect of Metallic Particles on Breakdown Voltage of N2 Gas in Uniform Field - Sreenath K; Rajesh Kamath B (International Journal of Engineering and Management Research, 2023)
Performance of the metal particles is determined by the breakdown voltage in N2 gas. The main factors which influence the breakdown in N2 are the shape, size, and different angles for uniform & non uniform field. Present work is intended to study the effect of metallic particles on breakdown voltage in N2 gas. Experiments have been carried out for different particles such as copper, aluminum & silver of 10 mm lengths are used under angle of 0°, 30°, 60°. Experimental results show that in copper and aluminium particles affect the insulation performance of N2 more than that with aluminum particle.